Central bank digital currency: Implications for liquidity management and monetary policy - Tom Bernhardsen; Arne Kloster (Norges Bank, 2023)
The paper discusses potential effects of a central bank digital currency (CBDC) on liquidity and monetary policy. CBDC could benefit the payment system but could also pose macroeconomic/financial challenges if demand for CBDC becomes high. High CBDC demand can affect banks' balance sheets, funding costs and the money and credit creation process, as well as the central bank's balance sheet and risk, and the implementation of liquidity and monetary policy. This may entail a substantial shock to the financial system as it functions today. These macroeconomic/financial costs are discussed in the literature. Much of the discussion focuses on how CBDC can be designed to contribute to a more efficient payment system, while avoiding or at least reducing the macroeconomic/financial drawbacks substantially. Proposed solutions include limiting the amount of CBDC that can be held, a multi-interest rate system for CBDC, a system where CBDC can be lost and where the central bank issues CBDC only in exchange for government securities. The benefits and costs of the first two in particular are discussed in this paper. We believe that both limits on CBDC holdings and multi-interest rates can help curb CBDC demand, but at the same time they will reduce the applicability of CBDC. (...)
hdl:11250/3166730
Keywords: 330